A Critical Review on the Book Contemporary Research Methods in the Humanities (Discussions on Politics of Method) - Leila Namdarian; Alireza Seghatoleslami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to critically evaluate the book Critical Review of the Book Contemporary Research Methods in the Humanities (Discussions on Politics of Method), by Ahmad Mohammadpour. The context for the formation of the most important theoretical and practical streams in the humanities and their ontological and epistemological aspects has been presented in this book. From this point of view, the book can be considered as a valuable document in this field. The main message of this book is that it is research methods derived from our worldviews and lifeworld that shape our understanding and interpretation of the world, and thus the author introduces a new concept called" Politics of Method ". The results of the review of this book show that the author has not been able to convey well the key and operational points about “Politics of Method " and his new findings; Therefore, this book is not able to provide guidelines for researchers in designing a research program from the perspective of methodology. Lack of connection between chapters, different language in presenting views and topics, inadequate translation of many parts of the book, are also among the weaknesses of this book.